2008
DOI: 10.1111/j.1751-7915.2008.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

tmRNA of Streptomyces collinus and Streptomyces griseus during the growth and in the presence of antibiotics

Abstract: SummaryStreptomycetes are soil microorganisms with the potential to produce a broad spectrum of secondary metabolities. The production of antibiotics is accompanied by a decrease in protein synthesis, which raises the question of how these bacteria survived the transition from the primary to the secondary metabolism. Translating ribosomes incapable to properly elongate or terminate polypeptide chain activate bacterial trans‐translation system. Abundance and stability of the tmRNA during growth of Streptomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The genome has a G + C content of 71.5%. The chromosome is predicted to contain 7.282 coding sequences, 5 rRNA clusters, 80 tRNA genes and one tmRNA gene ( Palecková et al, 2009 ). The analysis of the genome using antiSMASH software revealed that 29 gene clusters are involved in the biosynthesis of diverse secondary metabolites including terpenes, lanthipeptides, non-ribosomal peptides, and polyketides ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genome has a G + C content of 71.5%. The chromosome is predicted to contain 7.282 coding sequences, 5 rRNA clusters, 80 tRNA genes and one tmRNA gene ( Palecková et al, 2009 ). The analysis of the genome using antiSMASH software revealed that 29 gene clusters are involved in the biosynthesis of diverse secondary metabolites including terpenes, lanthipeptides, non-ribosomal peptides, and polyketides ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%